Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 133972 by liberty last updated on 26/Feb/21

H = ∫ (((2x−1)^7 )/((2x+1)^9 )) dx

H=(2x1)7(2x+1)9dx

Answered by EDWIN88 last updated on 26/Feb/21

 H = ∫ (((2x−1)/(2x+1)))^7 .(dx/((2x+1)^2 ))  change of variable let u = ((2x−1)/(2x+1))   du = (4/((2x+1)^2 )) dx ; (dx/((2x+1)^2 )) = (du/4)  H = ∫ (u^7 /4) du = (u^8 /(32)) + c = (1/(32))(((2x−1)/(2x+1)))^8  + c

H=(2x12x+1)7.dx(2x+1)2changeofvariableletu=2x12x+1du=4(2x+1)2dx;dx(2x+1)2=du4H=u74du=u832+c=132(2x12x+1)8+c

Terms of Service

Privacy Policy

Contact: info@tinkutara.com